The Discovery of Major Heart Risk Factors among Young Patients with Ischemic Heart Disease Using K-Means Techniques. - Sistani, Samane; Norouzi, Somayeh; Hassibian, Mohammad Reza; Tara, Mahmoud; Tabesh, Hamed; Hasibian, Sepideh; Dastani, Mostafa (International Cardiovascular Research Journal, 2019)
Background: Ischemic Heart Disease (IHD) is the leading cause of mortality in both developed and developing countries. It accounts for more than 15% of the total mortality worldwide. At the global scale, the massive occurrence of this disease can have tremendously negative effects on economy, especially among young people. Objective: The present study aimed to investigate the relationship between IHD and several important risk factors involved. It also looked into the prevalence of IHD among patients between 20 and 40 years of age. Methods: The present cross-sectional, retrospective survey was conducted in three referral heart hospitals affiliated to Mashhad University of Medical Sciences, Iran. The required data were extracted from integrated Hospital Information System (HIS) from 2010 to 2012. The data included clinical and demographic information, such as age, gender, marital status, occupation, diabetes, blood pressure, blood cholesterol, cigarette smoking, and family history. In the next phase, clustering technique and k-means algorithm were applied using the WEKA (3-6-9) software. Results: Totally, 88623 patients suffered from heart diseases between 2010 and 2012. When the specific inclusion and exclusion criteria were considered, the number of records was restricted to 776, which included 548 males. The clustering technique was done in two phases. Firstly, there were four clusters extracted and secondly, cluster analysis was done in terms of age and gender. According to the findings, cigarette smoking in males aged between 20 and 40 years was the main risk factor. Conclusion: The present research aimed to investigate the risk factors of heart diseases among patients between 20 and 40 years of age. Those below 40 years old were known as the main human resource in the community. The early prevalence of IHD in this population disabled them for the rest of their lives. This disability could also lead to irreparable physiological effects along with financial costs. It could also impose high costs on the society. Recognition of the risk factors of heart diseases at younger ages could contribute to healthcare policies.